2016
DOI: 10.1111/mmi.13327
|View full text |Cite
|
Sign up to set email alerts
|

The AP‐2 complex is required for proper temporal and spatial dynamics of endocytic patches in fission yeast

Abstract: In metazoans the AP-2 complex has a well-defined role in clathrin-mediated endocytosis. By contrast, its direct role in endocytosis in unicellular eukaryotes has been questioned. Here, we report co- immunoprecipitation between the fission yeast AP-2 component Apl3p and clathrin, as well as the genetic interactions between apl3Δ and clc1 and sla2Δ/end4Δ mutants. Furthermore, a double clc1 apl3Δ mutant was found to be defective in FM4-64 uptake. In an otherwise wild-type strain, apl3Δ cells exhibit altered dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 77 publications
(118 reference statements)
0
8
0
2
Order By: Relevance
“…cfr1 + exhibits genetic interaction with end4 + , suggesting a possible exomer role in endocytosis. Although the efficient FM4-64 uptake in cfr1D does not solely contradict this hypothesis because mutants in clathrin and AP-2 are able to internalize this dye (de León et al 2013(de León et al , 2016, this observation, together with the fact that Cfr1 is not observed at the PM (Figure 1), suggests that this function might be exerted after cargo internalization. It is possible that AP-2 contacts exomer at endosomes.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…cfr1 + exhibits genetic interaction with end4 + , suggesting a possible exomer role in endocytosis. Although the efficient FM4-64 uptake in cfr1D does not solely contradict this hypothesis because mutants in clathrin and AP-2 are able to internalize this dye (de León et al 2013(de León et al , 2016, this observation, together with the fact that Cfr1 is not observed at the PM (Figure 1), suggests that this function might be exerted after cargo internalization. It is possible that AP-2 contacts exomer at endosomes.…”
Section: Discussionmentioning
confidence: 71%
“…Western blots to detect soluble proteins were performed as described (Sharifmoghadam and Valdivieso 2009;de León et al 2016). To detect membrane proteins, the cleared lysates were incubated in the presence of 1.6 M urea in a tube rotator for 16 hr at 4°and the proteins were denatured at 65°for 5 min.…”
Section: Protein Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a more recent study it has been shown that clathrin contributes to the regularity of vesicle scission and vesicle size, but is not required for elongating or shaping the endocytic membrane invagination, but again the role of AP-2 was not studied (Kukulski et al, 2016). Finally, in S. pombe , the AP-2 α component (Apl3p) was shown to interact physically with clathrin light chain (Clc1p), and genetically with both Clc1p and the endocytic factor Sla2p and additionally apl3Δ null mutants showed altered dynamics of endocytic sites associated with abnormal cell wall synthesis and morphogenesis (de León et al, 2016; de León and Valdivieso, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…En S. cerevisiae se ha visto interacción física de la clatrina con el adaptador AP-1 pero no con los otros dos adaptadores (Lemmon and Traub, 2000;Yeung et al, 1999). En S. pombe por el momento sólo se ha detectado interacción física de AP-2 con clatrina (de Leon et al, 2016).…”
Section: Complejos Adaptadores (Aps)unclassified